The Correlation between Intraorifice Distance and the Anatomical Characteristics of the Second Mesiobuccal Canal of Maxillary Molars: A CBCT Study - Isabella Perondi; Silvio Taschieri; Martino Baruffaldi; Roberto Fornara; Luca Francetti; Stefano Corbella (Hindawi Limited, 2024)
Introduction. Missing anatomy is one of the main causes of endodontic failures, and accurate knowledge of teeth anatomy is a prerequisite for adequate root canal treatment. The aim of the present cone beam computed tomography (CBCT) study was to describe the anatomical characteristics of the mesiobuccal (MB) root canals of maxillary molars and to understand if a correlation exists between the position of the canal orifices and the anatomical features of the root. Methods. For the purposes of the study, a total of 100 CBCT scans of maxillary molars with two MB canals were selected and studied. The features of root canal anatomy of the MB root of the same teeth were analyzed and recorded (root length, confluence, and Vertucci classification). The distance between MB1 and MB2 orifices and the palatal orifice were recorded, as well as the distance between the orifices and the line joining the palatal orifice and the others. A statistical analysis was performed by providing descriptive measures, the measure of the correlation between different parameters, and the influence of some of these measures on the presence of a confluence between MB1 and MB2. Results. It resulted that the most frequent configuration is type II Vertucci. The length measured on the sagittal plane was significantly correlated to the presence of a confluence in the MB root. When the root length was higher than 14.56 mm, the confluence is three times more frequent than when the length is lower (OR = 3.635). The area under the curve (AUC) of the receiver operator characteristic (ROC) curve for length on the sagittal plane was 0.632 (P=0.036). Conclusions. The presence of a confluence between the MB canals of maxillary molars is correlated to the length of the root that could be measured on the sagittal plane and to the distance between the canal orifices. The relative position of the root canal orifices in relation to anatomic landmarks needs to be further explored.